Influence of tactics efficiency on results in serbian soccer super league in season 2009/2010 - Jankovic, A.; Leontijevic, B.; Jelusic, V.; Pasic, M.; Micovic, B. (Journal of Physical Education and Sport, 2011)
Objective. This research aims to compare the expression of football teams tactics, with different levels of performance, defined on the basis of placement on the table, after a competitive season. More precisely, it is necessary to determine whether and to what extent there are differences in the implementation of certain tactical assets (features) in the organization of successful attacks, among teams that are placed differently on the table. Methods. In the tactical analysis of expression of 12 teams divided into 3 groups based on placement on the table a total of 228 games in the 2009/2010 Super League in Serbia were covered. The first group (G1) consisted of the teams that took the top four place in the standings, the second group (G2) teams that were placed from 7th to 11th place and a third group (G3) consisted of four last placed teams. Observed parameters are related to the efficiency of pass games and the structure of successful attacks, attacks that have been completed by a shot to the goal. All observed parameters were conducted with specially made software, which is used to analyse football games. Results. By analysing the frequency of successful attacks, it was found that there is a statistically significant difference in the number of successful attacks among the teams that are placed differently on the table (p = 0.001), in favor of the better placed team. Also, the success of the attack, seen through their precision indicates the differences in their distribution (p = 0.025) among these groups. The results further suggest that the structure of attack is not related to the placement of the teams in the standings. However, the success of passing proved to be an important factor in achieving a better placement (p = 0.004), and the distance from which kick is directed at goal (p = 0.021). Conclusion. The results of this study may help to identify those tactic features in football, which contribute to achieving better results.